DECONSTRUCTION OF LEADING CHARACTERS IN ZOOTOPIA MOVIE SCRIPT - Batubara, Aina Sa'adah; Nasution, Siti Norma; Pratama, Diah Rahayu (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2020)
This study entitledDeconstruction of Leading Characters in ZootopiaMovie Script. This study discussed about Deconstruction of characters which aimed to deconstruct the opposition of major and minor characters in the movie script Zootopia, and also devalue the major and minor characters to be the new hierarchy. This research is based on the Deconstruction theory proposed by Jacques Derrida (Rodalphe Gasche : 1988), which systematize the steps in doing deconstruction analysis from the identifying the opposition hierarchy in the text that systematically privileged, then change or reverse that hierarchy, and the last was introduced a new term or idea, which apparently cannot be included in the page of old hierarchy category. The method used in this study was the descriptive qualitative method. The result of this research is uncovering the deeply complex foundation that is difficult to make sense, because there is no general truth or the permanent personality of each character, there will be the other side of character that can produced a new hierarchy.